2020
DOI: 10.3389/fnins.2020.583477
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Development of the Rodent Corticolimbic System

Abstract: In recent years, a growing body of research has shown sex differences in the prevalence and symptomatology of psychopathologies, such as depression, anxiety, and fearrelated disorders, all of which show high incidence rates in early life. This has highlighted the importance of including female subjects in animal studies, as well as delineating sex differences in neural processing across development. Of particular interest is the corticolimbic system, comprising the hippocampus, amygdala, and medial prefrontal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 330 publications
2
52
0
Order By: Relevance
“…This is particularly important limitation since over half the current astronaut class is female and there are sex-dependent differences in CNS sensitivity to charged particle radiation [9,82]. It is also important from a fundamental neurobiological perspective; female and male rodents differ in key developmental and behavioral aspects, in their response to stress, and in both their performance in and strategies for completing many "classical" behavioral paradigms [83][84][85][86][87]. Indeed, given the lower level of within-cage aggression in group-housed conspecific female vs. male mice (see next point), studies on female mice likely will have lower attrition than is reported here and elsewhere in male rodents [9].…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important limitation since over half the current astronaut class is female and there are sex-dependent differences in CNS sensitivity to charged particle radiation [9,82]. It is also important from a fundamental neurobiological perspective; female and male rodents differ in key developmental and behavioral aspects, in their response to stress, and in both their performance in and strategies for completing many "classical" behavioral paradigms [83][84][85][86][87]. Indeed, given the lower level of within-cage aggression in group-housed conspecific female vs. male mice (see next point), studies on female mice likely will have lower attrition than is reported here and elsewhere in male rodents [9].…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences in the development of the rodent corticolimbic circuit and its specific components has been recently elegantly reviewed ( Premachandran et al, 2020 ) and sex effects have been outlined at the level of the amygdala, mPFC and hippocampus in terms of differences in volume, morphology, synaptic organization, cell proliferation, microglia, and GABAergic signaling. Morphological and functional changes over the course of development have been studied mostly in the dorsal hippocampus, reporting both transient, and long-term effects of sex on this structure.…”
Section: Sex and Hemispheric Differences In Corticolimbic Development As Modulating Factors In The Effects Of Early Life Stressmentioning
confidence: 99%
“…Morphological and functional changes over the course of development have been studied mostly in the dorsal hippocampus, reporting both transient, and long-term effects of sex on this structure. Interestingly, females undergo an earlier switch in GABA A -mediated excitation to inhibition during the first postnatal week in rodents, occurring between PND4–7 compared to PND8–14 in males ( Premachandran et al, 2020 ). This difference in the timing of inhibition onset might be critical to determine further developmental processes in this structure and to identify potential windows of sensitivity to external stimuli.…”
Section: Sex and Hemispheric Differences In Corticolimbic Development As Modulating Factors In The Effects Of Early Life Stressmentioning
confidence: 99%
“…In humans, the mature state of these synapses is not reached until the onset of puberty in the hippocampus and the end of adolescence in the neocortex [ 103 ]. Although, it is expected that the mature characteristics of these synapses will be achieved more rapidly in females, compared to males in certain brain regions [ 104 ]. Therefore, similarly to the development of the GABA-driven force, drastic GABAergic synaptic development may also commence during infancy, however, this process may last significantly longer.…”
Section: Function and Development Of The Gabaergic Systemmentioning
confidence: 99%